PENGARUH KUALITAS HUBUNGAN SESAMA ANGGOTA TIM DAN KEPEMIMPINAN BERSAMA TERHADAP EFEKTIVITAS TIM PADA ORGANISASI PUBLIK - Anjar Ramdhana; Wustari L. Mangundjaya; Ahmad Cahyo Nugroho (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. This study aims to examine the effect of team member exchange qualities and shared leadership on team effectiveness in order to describe cross-functional integration conditions in public organizations. Cross-functional integration on these research explained with two points of view, as a group members behavior and as a team process. Cross-functional integration as a group members behavior established if (1) team member exchange qualities positively affects shared leadership; and (2) shared leadership positively affects team effectiveness. Cross-functional integration as a team process established if team member exchange qualities affects on team effectiveness through shared leadership. The study was conducted on Directorate A, B and C, with totally 90 respondents. The research method used regression analysis and path analysis. The results showed (1) team member exchange qualities positively affect shared leadership on Directorate A, B and C; (2) shared leadership positively affects team effectiveness on Directorate B and C; and (3) team member exchange qualities positively affects team effectiveness through shared leadership on Directorate C. Based on those results, we can conclude that cross-functional integration as group member behavior established in Directorate B and C, and cross-functional integration as a team process established only in Directorate C.